Catalogue of Ancient Near-Eastern Seals in the Ashmolean Museum. Volume I: Cylinder Seals - Buchanan, Briggs (1966)
Babylonian and Assyrian seals, from Proto-literate to Achaemenian period; peripheral regions: miscellaneous groups; Appendix on seal inscriptions; £7.7.0 (in U.K.).